2019
DOI: 10.1177/0037549719887790
|View full text |Cite
|
Sign up to set email alerts
|

Usage of solar shading devices to improve the thermal comfort in summer in a Romanian PassivHaus

Abstract: The global trend is to increase the thermal comfort in all kinds of buildings, residential and non-residential. At the same time, minimization of energy consumption and improved building sustainability must be achieved. Only precise calculations can keep the balance between maximizing comfort and minimizing energy consumption. The PassivHaus (PH) is a special type of building with low heating energy consumption that fulfills special requirements defined by the Passivhaus Institut of Darmstadt, Germany. The Pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…One of the obvious reasons for this was that about half of the survey respondents were seated at locations near to the windows and their sensations were recorded during the warmer time (around 1,300 to 1,500 h) of the day. The type of façade system and shading devices used in these spaces may have contributed to this result, as it was found that the type of shading could potentially affect thermal comfort and space cooling capacity (Udrea and Badescu, 2020). However, a contradicting result was obtained at which most of the occupants seated at this location found their thermal environment acceptable because they voted within the three central ratings (−1, 0, +1).…”
Section: Discussionmentioning
confidence: 99%
“…One of the obvious reasons for this was that about half of the survey respondents were seated at locations near to the windows and their sensations were recorded during the warmer time (around 1,300 to 1,500 h) of the day. The type of façade system and shading devices used in these spaces may have contributed to this result, as it was found that the type of shading could potentially affect thermal comfort and space cooling capacity (Udrea and Badescu, 2020). However, a contradicting result was obtained at which most of the occupants seated at this location found their thermal environment acceptable because they voted within the three central ratings (−1, 0, +1).…”
Section: Discussionmentioning
confidence: 99%
“…In tropical climates, the main strategy entails cooling and dehumidification [30]; in China, the use of an mechanical ventilation with heat recovery ( MVHR) system is essential [31], and for all types of climates in Germany, Romania, and Ukraine, energy demand increases as latitude increases, so this strategy aims to increase insulation levels based on location [32]. On the other hand, studies show that to achieve PH, it is necessary to place special emphasis on summer overheating and on shading strategies to achieve thermal comfort [33]. Given the outlined context, this study suggests incorporating the PH standard for housing in Chile through the addition of building construction improvements for housing situated across the country and reflecting various climates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, more suitable building materials can be used to alleviate summer overheating, but it is not applicable to buildings that have been put into use. The existing research by Udrea et al [26] and Sun et al [27] showed that the building shading design can effectively alleviate the phenomenon of overheating in summer, and has the advantages of being economical, wide applicability, and high comfort. Because the external shading devices of the building can block the solar radiation outdoors, the shading effect is better than the internal shading devices effect [28], and there is no need for human control.…”
Section: Introductionmentioning
confidence: 99%